2022
DOI: 10.1088/2752-664x/aca76c
|View full text |Cite
|
Sign up to set email alerts
|

Does renewable energy consumption reduce energy ecological footprint: evidence from China

Abstract: The modern economic growth paradigm relies heavily on natural endowments. Renewable energy as a permanent energy source has the potential to reduce the ecological footprint. We adopt the Vector Autoregressive model to examine the impact of renewable energy consumption on the energy ecological footprint and use the quantile regression method to test the heterogeneity and asymmetry between energy ecological footprint and photovoltaic, wind energy, and biomass energy. The results show that renewable energy has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Multiple studies have examined the correlation between the utilization of renewable energy and the impact on the environment. A few of them concluded that the use of renewable energy leads to a reduction in the ecological footprint [75]. In addition, Usman et al [76] discovered negative impacts of renewable energy and innovation on the ecological footprint.…”
Section: Determinants Of Ecological Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have examined the correlation between the utilization of renewable energy and the impact on the environment. A few of them concluded that the use of renewable energy leads to a reduction in the ecological footprint [75]. In addition, Usman et al [76] discovered negative impacts of renewable energy and innovation on the ecological footprint.…”
Section: Determinants Of Ecological Footprintmentioning
confidence: 99%
“…Alola et al [121] found that renewable energy utilization has a positive effect on ecological footprint at certain quantiles, indicating a complex relationship between renewable energy consumption and ecological footprint. However, Nan, Sun, Mei, Yue and Yuliang [75] found that renewable energy consumption has a long-term negative effect on the ecological footprint in China, suggesting that increasing renewable energy consumption can lead to a decrease in the ecological footprint. Sharif et al [122] found that renewable energy decreases the ecological footprint over long term for each quantile in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utilization of RE sources has demonstrated a significant influence on the mitigation of the ecological footprint in diverse geographical regions [39]. The utilization of RE sources has garnered substantial empirical evidence, thereby substantiating its advantageous influence on the conservation of natural resources [39,40]. Alternatively, non-RE sources lead to increased exploitation of limited resources, such as coal and oil, thereby exacerbating the degradation of the environment [35].…”
Section: Background Of the Studymentioning
confidence: 99%
“…The relationship between clean energy consumption (CEC) and ecological footprint is multifaceted, as they are intricately linked in terms of their implications for the sustainability of human activities and their environmental consequences. The utilization of clean energy sources, including wind, solar, hydro, and nuclear power, has been observed to yield significantly lower quantities of greenhouse gas emissions in comparison to conventional fossil fuels such as coal, oil, and natural gas [40]. The augmentation of CE has the potential to yield substantial reductions in carbon emissions, thereby mitigating the adverse effects of global warming and climate change.…”
Section: Clean Energy Consumption and Ecological Environmentmentioning
confidence: 99%
“…The relationship between renewable energy use and environmental impact has been extensively studied in the empirical literature. The majority of research articles listed in Table 3, including works by Philip et al [29], Sahoo and Sethi [36], Nathaniel et al [45], Usman et al [46], Wang et al [47], Rej et al [48], Abid et al [49], Raza et al [50], Nan et al [51], Wang et al [52], and Abban et al [53], have demonstrated a negative impact of renewable energy use on environmental impairment. However, studies by Raghutla et al [54] and Karada g Albayrak et al [55] identified a positive impact of renewable energy utilization on environmental impairment, while Tiwari et al [56] reported an insignificant relationship between ecological footprint and renewable energy use.…”
Section: Empirical Literature On the Environmental Effects Of Renewab...mentioning
confidence: 99%